2012
DOI: 10.3109/01443615.2012.714017
|View full text |Cite
|
Sign up to set email alerts
|

Maternal serum cholesterol levels are elevated from the 1st trimester of pregnancy: A cross-sectional study

Abstract: Cholesterol is monitored in the non-pregnant adult population, where normal values are established. Although reported to be elevated in pregnancy, cholesterol is neither routinely measured nor treated. We aimed to investigate cholesterol levels throughout pregnancy and to establish reference values for cholesterol in healthy pregnant women. This was a cross-sectional analysis of serum cholesterol in healthy women with an uncomplicated singleton pregnancy. Pregnant women attending for antenatal care were recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 34 publications
4
45
2
1
Order By: Relevance
“…The present data indicate that blood lipid concentrations also increase in line with this. The increase in serum lipids during pregnancy has been shown in previous research [10–13] with one group of researchers finding that a mother’s serum cholesterol concentrations rise by approximately 50–70% during pregnancy compared to normal concentrations [27]. Others have reported that, compared to non-pregnant women, estimated total cholesterol concentrations increase up to 39% in late pregnancy and triglyceride concentrations may be anywhere up to 138% higher than non-pregnant concentrations in late pregnancy [12].…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…The present data indicate that blood lipid concentrations also increase in line with this. The increase in serum lipids during pregnancy has been shown in previous research [10–13] with one group of researchers finding that a mother’s serum cholesterol concentrations rise by approximately 50–70% during pregnancy compared to normal concentrations [27]. Others have reported that, compared to non-pregnant women, estimated total cholesterol concentrations increase up to 39% in late pregnancy and triglyceride concentrations may be anywhere up to 138% higher than non-pregnant concentrations in late pregnancy [12].…”
Section: Discussionmentioning
confidence: 54%
“…Others have reported that, compared to non-pregnant women, estimated total cholesterol concentrations increase up to 39% in late pregnancy and triglyceride concentrations may be anywhere up to 138% higher than non-pregnant concentrations in late pregnancy [12]. Evidence has shown that blood lipids revert to pre-pregnancy levels after delivery which suggests that the elevated serum lipids could play an important role in fetal development [12,13,27]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Availability of lipids to the fetoplacental unit depends on de novo synthesis by the foetus as well as maternal transfer. Cholesterol, for example, can reach the foetal circulatory system after crossing the syncytiotrophoblast as LDL-c [49,55]. In pig foetuses, fatty acid availability and composition depend more on foetal synthesis from precursors transferred from the mother than on direct maternal transfer [56,57,58,59,60,61], since fatty acids do not easily cross the placenta in ruminants, pigs or horses [62].…”
Section: Discussionmentioning
confidence: 99%
“…Although cholesterol levels are often elevated during pregnancy, cholesterol is generally not evaluated or treated. A study by Bartels et al confirmed that cholesterol levels elevate beginning in the first trimester and continue throughout pregnancy 33 . It is not clearly established at what point after delivery should cholesterol levels be measured in women, but measurement at least 12 weeks post-partum and post-lactation cessation seems reasonable.…”
Section: Current Guideline Recommendationsmentioning
confidence: 89%